URAL CLERGY ASSISTANCE OFFERED TO THE RUSSIAN ARMY IN THE YEARS OF RUSSO-JAPANESE WAR - Nechaev, M.G. (Perm Federal Research Centre Journal, 2015)
The Russo-Japanese war of 1904-1905, so unfortunate for Russia, was considered by historians to signal the beginning of the Russian Empire decline. A critical component in assessing these events prevented from applying a thorough and systematic approach to studying both the progression of the hostilities and the transformations that arose in the course of this protracted and unpopular war. The church provided real support and assistance for the fighting army at the rear and at the front. However, both contemporary researchers and those of the later period underestimated the social significance of the Church efforts to protect not only the State, but the Russian society on the whole. Based on the materials of five Ural dioceses, the paper reconstructs and analyses the scale of the clergy’s assistance offered to the army in the years of the Russo-Japanese war.